Employability of graduates in Library and Information Science five years after graduation - Borrego, Ángel; Comalat, Maite (Anuario ThinkEPI, 2021)
This article summarizes results related to graduates in Library and Information Science (LIS) provided in a report on higher-education employability published by the Spanish National Statistics Institute (INE) in 2019. The data show that LIS graduates have a slightly lower employment rate than other graduates. Nevertheless, they enjoy greater job stability, with a higher percentage of permanent contracts instead of placements or internships. More than one-quarter of LIS graduates work part-time, and the Public Administration continues to be the sector providing more employment opportunities for them. A certain level of overqualification is observed, with significant percentages of LIS graduates stating that they hold positions for which their degree is not necessary. Salaries are lower than those of other graduates, with data showing the same gender pay gap that affects female graduates across all disciplines. LIS graduates are satisfied with their training, and most would study the same degree again. They are little inclined to international mobility during their studies and consider themselves advanced users of information and communication technologies.